2005
DOI: 10.1093/humupd/dmi013
|View full text |Cite
|
Sign up to set email alerts
|

Androgen excess fetal programming of female reproduction: a developmental aetiology for polycystic ovary syndrome?

Abstract: The aetiology of polycystic ovary syndrome (PCOS) remains unknown. This familial syndrome is prevalent among reproductive-aged women and its inheritance indicates a dominant regulatory gene with incomplete penetrance. However, promising candidate genes have proven unreliable as markers for the PCOS phenotype. This lack of genetic linkage may represent both extreme heterogeneity of PCOS and difficulty in establishing a universally accepted PCOS diagnosis. Nevertheless, hyperandrogenism is one of the most consis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
355
1
28

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 474 publications
(396 citation statements)
references
References 184 publications
12
355
1
28
Order By: Relevance
“…This supports the concept that fetal growth retardation, an early marker of adult diseases, can be initiated through prenatal excess exposure to sex steroids. Studies in nonhuman primates and other animals have shown that prenatal exposure to testosterone led to female hyperandrogenism (19), infertility (22,23), behavior modifications (24) abdominal adiposity (25) and insulin resistance (17) during adulthood in the offspring. In all these studies, testosterone was administered to otherwise normal pregnant female animals and hence the increase in circulating maternal testosterone was of exogenous origin and not caused by any maternal disease.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This supports the concept that fetal growth retardation, an early marker of adult diseases, can be initiated through prenatal excess exposure to sex steroids. Studies in nonhuman primates and other animals have shown that prenatal exposure to testosterone led to female hyperandrogenism (19), infertility (22,23), behavior modifications (24) abdominal adiposity (25) and insulin resistance (17) during adulthood in the offspring. In all these studies, testosterone was administered to otherwise normal pregnant female animals and hence the increase in circulating maternal testosterone was of exogenous origin and not caused by any maternal disease.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, maternal testosterone may only be a biomarker for fetal growth. However, assisted by the available animal data on the effect of the exertion of exogenously administered testosterone on otherwise normal pregnancies (19), we hypothesize that the association between maternal testosterone levels and reduced birth size is a direct effect of increased maternal androgen levels. Probably, it is mediated by one or more of the above possible mechanisms and is not just a chance-coincidental phenomenon.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In females, antenatal exposure of sheep and monkeys to androgens has been shown to cause a polycystic ovarian syndrome (PCOS)-like phenotype, although this as a potential cause of PCOS and is highly speculative (Abbott et al 2005). Furthermore, there is evidence for a direct effect of some pesticides on ovarian function.…”
Section: Introductionmentioning
confidence: 99%
“…En los últimos años se ha propuesto que la programación fetal podría estar implicada en la patogenia del SOP. En este contexto la exposición prenatal a andrógenos (EPA) podría ser uno de los principales candidatos como factor reprogramador [13][14][15][16][17][18][19][20] . Independiente de la fuente del exceso de andrógenos prenatal, estas observaciones sugieren que el SOP podría ser programado in utero por la influencia del aumento de andrógenos e insulina, posiblemente mediante la alteración de la expresión génica durante la vida pre y post-natal.…”
unclassified